2010
DOI: 10.1177/1087057109359196
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Estrogen Receptor TR-FRET Assay for Simultaneous Measurement of Steroid Site Binding and Coactivator Recruitment

Abstract: The human estrogen receptors (hER) are members of the nuclear hormone receptor (NHR) superfamily and represent important drug targets for the pharmaceutical industry. Initially, ligand binding assays were used to identify novel ligands using receptors purified from native tissues. With the advent of molecular cloning techniques, cell-based transactivation assays have been the gold standard for many years of drug discovery. With the elucidation of the structural mechanisms underlying the activation of NHRs, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
1
22
0
2
Order By: Relevance
“…Optical methods have previously been used to study ER homo-and heterodimerization in cell-free in vitro systems and in intact cells (24,29); however, none of these approaches could potentially be used to study the same process in living animals (31). In earlier work, we used fluorescence resonance energy transfer and excimer-emission methods to study the effect of ligand binding on the kinetic and thermodynamic stability of ER␣ homodimers in vitro and the additional stabilizing effect due to coactivator binding to ER-agonist complexes (19,32,33).…”
Section: Bioluminescence Imaging Of Er Dimer Formation In Vivomentioning
confidence: 99%
“…Optical methods have previously been used to study ER homo-and heterodimerization in cell-free in vitro systems and in intact cells (24,29); however, none of these approaches could potentially be used to study the same process in living animals (31). In earlier work, we used fluorescence resonance energy transfer and excimer-emission methods to study the effect of ligand binding on the kinetic and thermodynamic stability of ER␣ homodimers in vitro and the additional stabilizing effect due to coactivator binding to ER-agonist complexes (19,32,33).…”
Section: Bioluminescence Imaging Of Er Dimer Formation In Vivomentioning
confidence: 99%
“…Historically, screening assays for smallmolecule modulators of nuclear hormone receptors are often based on ligand-sensitive interaction with transcriptional coactivators and corepressors. [31][32][33] It has been shown that apo-NR2E3 is capable of interacting with corepressors N-CoR, SMRT, and RetCOR. 22,26 Given that NR-corepressor interaction is agonist sensitive for the vast majority of NRs, we developed a cell-free HTS-compatible TR-FRET assay for small-molecule NR2E3 modulators, which is based on agonist-induced disruption of the interaction between GSTtagged apo-NR2E3 and MBP-tagged fragment of transcriptional corepressor RetCOR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a tr-FRET assay [16, 17] of this design is very useful to quantitatively probe the ability of new ligands to form a complex with the ER that is capable of recruiting coactivator, an important indicator of an active biological complex. This assay can be performed in two ways: coactivator titration into a preformed ER-ligand complex measures the affinity of the coactivator.…”
Section: Resultsmentioning
confidence: 99%